(3eWGdY GdCfhGQ Ydi UMjM GdGKGQs - (3GHf bQbhd , EHQGgje Hf jhSa Hf GOge GdhgQGfj, CHh ESMGb,J (B569 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eXgQ Ojfg Ydi cd Ojf , hMGFWg ef THg GdeHWdjf hHGYK QShdg GdCejf Edi cGaI GdNdb CLeYjf MOKfG GdeYGaQi s
(3BNQgG (B:s
(3hddCUjdi JQc GdSMhQ , hGdChd gh GdUhGH hYdjg jOd eG JMJ GdJQLeI , hGddg GYde Je GdcJGH s
(3Hg GfXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B129s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs